The determination of the optimum conditions upon the leaching performance of calcined magnesite. Issue 11 (November 2019) - Demir, Fatih; Dönmez, Bünyamin
Abstract: The aim of the study is to examine the reaction of calcined magnesite in the citric acid media, and after that it is determination of optimal conditions about the leaching performance of calcined magnesite by an experimental plan of Taguchi Statistical Method with L16 (4 5 ). The parameters such as particle size, reaction temperature, acid concentration, solid–liquid ratio and reaction period are tested. In this work, the optimal combination of the parameters that achieves robustness against noise factors is found as: 50 °C, 45 min, -319 μm, 0.125 g/mL, and 2M, respectively. Extraction efficiency of the magnesium from calcined magnesite is 98.86 %. Abstract : Materials science; Dissolution performance; MgO; Optimization; Citric acid